Estudo do Comportamento do Aço Inoxidável Austenítico AISI 321 Nitretado e Nitrocementado a Plasma Sob Solicitações de Desgaste, Corrosão e Fadiga - Manfrinato, Marcos Dorigão (2023)
The AISI 321 austenitic stainless steel is used in the chemical, petrochemical and fertilizer industries, as it can operate at high temperatures (above 600 °C) and under corrosive media. However, it has poor tribological properties. Thermochemical plasma nitriding and nitrocarburizing treatments are used to increase surface hardness, fatigue resistance, wear resistance and not deteriorate its pre-existing corrosion resistance. Treatment parameters such as time, temperature, gas mixture and pressure can change the composition of the layer formed in plasma nitriding and nitrocarburizing treatments. The present work aimed to evaluate the influence of plasma nitriding and nitrocarburizing temperatures on the formation, microstructure and ductility of layers in AISI 321 austenitic stainless steel and verify their performance when subjected to cyclic polarization corrosion, abrasive microwear with fixed sphere, rotary bending fatigue, spherical contact fatigue and multiple scratching and indentation tests. X-ray diffraction demonstrated that the expanded austenite phase rich in interstitial solutes (nitrogen and carbon) formed on the surfaces treated at 400 °C and that, for treatments at 500 °C, this phase decomposed into CrN and '-Fe4N. The expansion of the crystal lattice at 400 °C was greater for the nitrocemented samples than for the nitrided ones, both samples had the same layer depth. At 500 °C, the layer depth was greater for the nitrocemented samples, as was the layer hardness. In the cyclic polarization corrosion test in a medium of 3.5% NaCl, the nitrocarburizing treatment showed the highest corrosion potential (Ecorr) and the highest pitting potential (Epite) about the other treatments, therefore presenting the greatest resistance to corrosion. Corrosion resistance was lower for treatments carried out at 500 °C to the base material. For mechanical behavior and wear tests, all layers performed better than the base material. In nanohardness measurements, the relationships between hardness (H) and apparent modulus (E), the H/E and H3/E2 relationships indicate the deflection capacity, the capacity to absorb elastic energy and plastic work. The nitrocemented layer at 400 °C showed greater ductility and greater deformation capacity, without showing spalling or cracking, which resulted in better performance in the spherical contact fatigue test, the lowest wear rate 3.95x10-7 mm3/Nm, high fatigue limit (280 MPa), as the layer presents greater plastic work on the surface. In terms of resistance to microwear, treatments at 500 °C showed lower wear resistance than treatments carried out at 400 °C due to greater brittleness resulting from the decomposition of expanded austenite into ’-Fe4N and CrN. Microcracking and peeling of the layer were the wear mechanisms observed in the abrasive microwear tests with a fixed sphere, rotary bending fatigue, spherical contact fatigue and multiple scratching tests. The layer nitrocemented at 500 °C presented a higher fatigue limit (285 MPa) as it presented the greatest layer thickness, lowest transition gradient and hardness throughout the layer, greatest hardness and therefore probably presents the highest level of compressive residual stress that contributed to this greater value. The hybrid treatment of nitrogen and carbon diffusion, nitrocarburizing, at 400 °C showed the best performance in the corrosion test, spherical contact fatigue, abrasive microwear and scratching test as the layer has greater ductility.